Analisis Minat Mahasiswa Memilih Program Studi Akuntansi Universitas Mikroskil Dengan Theory of Planned Behavioral - Syafira Ulya Firza; Agustina Agustina; Devina Loman (Politeknik Ganesha Medan, 2022)
Accounting is one of the oldest science but plays an important role in the industrial. This will certainly attract intention in choosing the Accounting study program. However, in reality, during the last 4 years, student’s intention in choosing the Accounting study program at the Mikroskil University has actually decreased. For this reason, this research aims to examine and analyze the factors that influence student’s intention in choosing the Accounting study program at the Mikroskil University. This research was conducted using the Theory of Planned Behavioral. The study began by distributing questionnaires and continued into testing with the partial least square research method using the SmartPLS. The results obtained, Attitude and Perceived Behavioral Control have a positive effect on student’s intention. Meanwhile, Subjective Norms have no influence on students' intention in choosing the Accounting study program at the Mikroskil University. In addition, based on the moderation test, it was found that Perceived Behavioral Control was unable to moderate the relationship between Attitude and Subjective Norms with student’s intention in choosing the Accounting study program at the Mikroskil University. Based on the results of this study, the suggestions for improvement that can be given are to maintain and, if possible, improve the academic quality and existing facilities to increase the attitude also carry out activities that can improve the Perceived Behavioral Control. By increasing those things, student's intention in choosing the Accounting Study Program is expected to increase.